Performance Evaluation of Multicarrier Based Techniques for Single Phase Hybrid Multilevel Inverter using Reduced Switches - Nunsavath Susheela; P. Satish Kumar (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
The multilevel inverters are very popular in high power high voltage applications. However the multilevel inverters has some demerits such as requiring higher number of components, PWM control method is complex and capacitor voltage balancing problem. The hybrid multilevel inverter presented in this paper has superior characteristics over conventional multilevel inverters. The hybrid multilevel inverter employs fewer components and less carrier signals when compared to conventional multilevel inverters. It consists of level generation and polarity generation stages which involves high frequency and low frequency switches. The complexity and overall cost for higher output voltage levels are greatly reduced. Implementation of single phase 7-level, 9-level and 11-level hybrid multilevel inverter has been performed using sinusoidal pulse width modulation (SPWM) strategies i.e., phase disposition (PD), alternate phase opposition disposition (APOD) and carrier overlapping (CO). Also the three techniques are compared in terms of total harmonic distortion (THD) for various modulation indices and observed to be greatly improved when compared to conventional topologies. The performance of single phase eleven level hybrid inverter is analyzed for different loads.  Simulation is performed using MATLAB/ Simulink.